Fintech Adoption and its Impact on Financial Inclusion: a Survey-Based Analysis of Rural Entrepreneurs in Tanzania - Abraham Charles Nathanael; Magwana Ibrahim Ngollo (KEUNIS, 2026)
This study explores the impact of fintech adoption on financial inclusion among rural entrepreneurs in Tanzania, with a focus on the roles of digital literacy and financial awareness. The study employed Partial Least Squares Structural Equation Modeling (PLS SEM). Employing a quantitative research design, data was collected from rural business owners to assess the impact of technological engagement on access to financial services. The findings indicate a strong, statistically significant correlation between fintech adoption and enhanced financial inclusion, highlighting fintech's potential to address existing financial access disparities. Importantly, digital literacy was found to have a statistically significant moderating effect, enhancing the impact of fintech adoption on financial inclusion. Furthermore, digital literacy and financial awareness were identified as critical enablers, significantly affecting the effective utilization of fintech platforms. However, the benefits of fintech adoption are not uniformly experienced, varying according to socioeconomic and contextual factors. The study underscores the necessity for a comprehensive strategy that integrates technological access with tailored educational initiatives and inclusive policy interventions. This research enriches the existing literature on digital finance and provides valuable insights for policymakers, fintech providers, and development practitioners dedicated to promoting inclusive economic growth in underserved communities.